THE USE OF 321 STRATEGI IN TEACHING A PASSAGE - VASCOLINO PATTIPEILOHY; FEBIYOLA WIJAYA (CV KULTURA DIGITAL MEDIA, 2023)
At school, the success of comprehending a text becomes a problem, based on what the researcher witnessed during the observation in State Polytechnic of Ambon, Commerce Department. Students were given a text including a passage and a dialogue then they had to read and understand it in order to answer the questions given individually. Thus, the students should comprehend the passage in their own way. The 321 strategies offer students to comprehend the passage in their own way. The three easy steps in the approach will stimulate the students to be active rather than the teacher. The procedure of the research is as follow: first, administrating pre test to measure student basic knowledge. Second, giving treatment which is the 321 strategy and finally, administrating post test to see the result of giving treatment to see the students’ improvement.